Gambaran Resiliensi pada Orang dengan HIV/AIDS (ODHA) yang Tergabung dalam Supporting Group di Kabupaten Jember - Arif Gustyawan; Emi Wuri Wuryaningsih; Dicky Endrian Kurniawan (UPT Percetakan dan Penerbitan Universitas Jember, 2022)
Increasing the number of (PLWHA) makes many problems that affect health, social, and psychological problems. Support Groups (SG) as a means of PLWHA in realizing a resilient attitude. The purpose of this study was to describe resilience among people living with HIV/AIDS (PLWHA) who are members of a supporting group in the Jember Regency. This study used a descriptive design with sampling techniques using purposive sampling. Data were analyzed by descriptive and frequency with a sample of 100 samples. Data retrieval was done by a Brief Resilience Scale questionnaire. The results of this study show that the majority of respondents are in the normal category, as many as 56 respondents (56%). High reliability due to internal and external support The external factors possessed by respondents which made respondents more resilient were family support, especially and support from fellow PLWHA who were members of a supporting group. resilience for PLWHA should be further enhanced to help PLWHA survive better and be able to face difficulties.